Analysis Energy of Freeze Vacuum Drying System with Thermal Energy Storage and Reverse Valve of 4kg Capacity - NST, Berriansyah Cipta; Cahyati, Wulan; Mainil, Rahmat Iman; Martin, Awaludin (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2025)
This research evaluates the energy efficiency of the Aloe vera drying process using a Freeze Vacuum Drying (FVD) system, focusing on the thermal performance and the role of a Thermal Energy Storage (TES) unit with paraffin wax as the storage medium. Experiments were conducted with Aloe vera samples of 2 kg, 3 kg, and 4 kg to assess their effects on energy usage, Coefficient of Performance (COP), and moisture removal efficiency. The highest Specific Moisture Extraction Rate (SMER) was 0.132 kg.water/kWh for the 4 kg sample, with a Specific Energy Consumption (SEC) of 7.223 kWh/kg.water and a COP of 5.4. The energy efficiency peaked at 10.80%, achieved by incorporating TES. The results demonstrate that TES improves COP and reduces the specific energy demand, leading to a more energy-efficient drying process.